Aplikasi SIPKROS Sebagai Upaya Pencegahan dan Penanganan Kekerasan Seksual Di Salah satu Sekolah Menengah Pertama di Kab. Brebes - Lufia Krismiyanti; Purwo Susongko (Universitas Pancasakti Tegal, 2026)
Based on case records from guidance counselors at SMP Negeri 1 Brebes in 2024, three cases of sexual violence were recorded by ninth-grade students. This data prompted the school to develop the SIPKROS application. This study aims to describe the process of using the SIPKROS (Student Reproductive Health Information and Complaint System) application and its impact on preventing and addressing sexual violence against students. The author collaborated with other teachers in designing SIPKROS. The impact of SIPKROS use was measured using an open-ended questionnaire and analyzed using a Likert scale. The impact of SIPKROS on homeroom teachers was that it made homeroom guidance materials and morning assembly more focused because it was equipped with learning tools. The results of the student questionnaire showed that 63% understood the actions of refusing, reprimanding, terminating relationships, and reporting when sexual violence occurs. One month after SIPKROS was implemented, there were no reports of sexual violence at SMPN 1 Brebes. This study concludes that SIPKROS can be used as a solution for preventing and addressing sexual violence against students.